(untitled) (Teaching and Learning Inquiry, 2021)
This study examines the lived experiences of seven internationally diverse scholars from Canada, the United States, New Zealand, and Australia to answer the question: how do we make meaning of our collective boundary crossing experiences across disciplines and positions within SoTL? Our positions range from graduate student, faculty, and academic developers, to department chair and centre director. We conducted a phenomenological study, based on narratives of experience, and drew on Wenger-Trayner and Wenger-Trayner’s (2015) theoretical framework that explores the features of a landscape of practice. Guided by this framework, we analyze our boundary crossings and brokering across the “diverse, political and flat” features of the SoTL landscape. Our collective findings highlight the critical role brokers play in facilitating boundary crossings. Brokering is precarious, bringing people together, building trusting relationships, and developing legitimacy while negotiating deadlocks, bureaucracy, authorities, and a multitude of challenges. Brokers, we found, require strength and resilience to mobilise, influence, and drive change in the landscape to transform existing practices or create new ones. We suggest that our analytical process can be used as a tool of analysis for future research about how brokers influence the SoTL landscape of practice and how brokering enhances SoTL development, support, and leadership.